Dose-effect relationship of different acupuncture courses on chronic insomnia disorder: study protocol for a randomized controlled trial - Zhu, Fengya; Liu, Junqian; Wang, Yuan; Ma, Tingting; Wang, Tianyu; Yang, Bin; Miao, Runqing; Wu, Jie (Frontiers in Psychiatry, 2023)
Background: Chronic insomnia disorder (CID) is increasing in prevalence year by year, is long lasting, and potentially risky. Acupuncture has been widely used in the clinical management of this condition. However, there is still a lack of direct evidence on the dose-effect relationship between different acupuncture courses and clinical efficacy. To identify this relationship, we will design a randomized controlled trial to clarify the difference in efficacy of different acupuncture courses for CID.Methods and design: This is a prospective, parallel, single center randomized controlled trial. 201 participants with CID will be randomly divided into three groups (Group A, Group B, and Group C).The three groups will be given acupuncture therapy for 4, 6, and 8 weeks, three sessions per week, with at least one day between sessions. Follow-up will continue until the third month after the end of treatment. The primary outcome is the Insomnia Severity Index (ISI), and secondary outcomes include percentage of ISI < 8 points, the Pittsburgh Sleep Quality Index (PSQI), Self-Rating Anxiety Scale (SAS), Self-Rating Depression Scale (SDS), Fatigue Severity Scale (FSS), medication use, and safety.Discussion: This study is expected to provide direct evidence for the optimal treatment cycle of acupuncture for CID, as well as to facilitate health economic evaluation.Clinical trial registration: ChiCTR2300073711.